Development of Auditory Intellectually Repetition (AIR) Based Student Worksheets for Science Subjects at SMPN 6 Sikur - Urwatil wutsqo amry; Baiq Anita Febriana; Lisawati (urn:asian://2988-7534asian.v3i37)
This study aims to develop Auditory Intellectually Repetition (AIR) based Student Worksheets (LKPD) for seventh grade science subjects at SMPN 6 Sikur which are valid based on graphical aspects, content feasibility, presentation feasibility, and linguistic aspects. This study uses the type of development (Research & Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research was carried out until the Implementation stage and followed by teacher and student response tests. The research object is a Student Worksheet based on Auditory Intellectually Repetition (AIR). The data collection instrument is a validation sheet filled out by 2 expert validators and one science teacher. The results of the data analysis obtained a validity score from the graphical aspect of 92.36%, content feasibility of 91.68%, presentation feasibility of 89.58%, language of 93.75%, and a total average value of 91.84% with the criteria of "Good/Valid/Feasible". The LKPD that had been validated by the validator was tested on 33 students and obtained a response result of 86.87% with valid/feasible criteria, as well as 1 science teacher and obtained a score of 86.48% with valid/feasible criteria. Based on the results of the data analysis, it was concluded that the LKPD based on Auditory Intellectually Repetition (AIR) that was developed was valid and could be applied in the learning process in science subjects.